Achieving zT > 2 in p‐Type AgSbTe2−xSex Alloys via Exploring the Extra Light Valence Band and Introducing Dense Stacking Faults. Issue 9 (18th December 2017) - Hong, Min; Chen, Zhi‐Gang; Yang, Lei; Liao, Zhi‐Ming; Zou, Yi‐Chao; Chen, Yan‐Hui; Matsumura, Syo; Zou, Jin
Abstract: Through simultaneously enhancing the power factor by engineering the extra light band and enhancing phonon scatterings by introducing a high density of stacking faults, a record figure‐of‐merit over 2.0 is achieved in p‐type AgSbTe2− x Se x alloys. Density functional theory calculations confirm the presence of the light valence band with large degeneracy in AgSbTe2, and that alloying with Se decreases the energy offset between the light valence band and the valence band maximum. Therefore, a significantly enhanced power factor is realized in p‐type AgSbTe2− x Se x alloys. In addition, transmission electron microscopy studies indicate the appearance of stacking faults and grain boundaries, which together with grain boundaries and point defects significantly strengthen phonon scatterings, leading to an ultralow thermal conductivity. The synergetic strategy of simultaneously enhancing power factor and strengthening phonon scattering developed in this study opens up a robust pathway to tailor thermoelectric performance. Abstract : The extra light valence band and dense stacking faults ensure a figure‐of‐merit over 2 in AgSbTe1.85 Se0.15 . Alloying with Se decreases the energy offset between the light and the primary valence bands, leading to an enhanced power factor. Transmission electron microscopy studies reveal the dense stacking faults and grain boundaries, which significantly strengthen phonon scatterings, generating an ultralow thermal conductivity.